Ontologic Planning - Alkan, Ahmet (ICONARCH International Congress of Architecture and Planning, 2017)
Debates about “being” and “existence” have continued uninterruptedly since ancient times in accordance with the evolution of philosophical thinking albeit at various levels of intensity. “Spatial Planning” which had not constitute a problem area for mankind until the industrial revolution, was linked to “ontology” either. In the post industrial revolution, on the other hand, “Cultural Delay” was regarded as a threshold before harmony in defining social problems mostly as a result of “technology-culture” oriented approaches. Failure to obtain expected results from endeavors to find solution to spatial problems in this manner of relationships paved the way for emergence of new ideas with regard to making use of ontology. However ontology has not been able to find a place for itself within the planning discipline and theory in adequate scope and dimensions in the search for a solution to the problem. This paper will make an attempt at presenting a point of view that can a modest contribution to the planning and ontology relations and try to discuss whether or not such endeavors will evolve into a method. The theme of planning, which began and was tried to be continued as “people-oriented”, also carries an “ontological” approach at the heart of the action. The problem here is to find an answer to the question of how an institutionalized structure or system can be acquired by raising this improvised attitude to the level of consciousness, thereby enabling it to participate effectively in the planning-implementation efforts. We are now faced with the reality that the efforts that were made from the beginning of the industrial revolution, when urban developments gained momentum, to the Euclidian understanding of planning in the 1950s and 1960s based on scientific approaches, to an approach of planning that channelled limited urban lands to profit during the urbanization process, to making “strategic” decisions on the basis of the planning decision theory and gradually evolving into a search for “strategic spatial planning” have not yielded the anticipated results. Can we make use of “ontology” in finding a solution to this deep-rooted and complicated question? If yes, how? Can macro and micro level institutional structures be used as instruments to this end, no matter how utopian they may seem today? Can existing ones be rendered more effective? Is it possible that there might be some among the variables of the planning (dependent and independent) that need to be opened for discussion and repositioned (like time)? Is it possible to redefine ontology within the hierarchical structure of planning? We are going to seek answers to some of these questions within the limited scope of this paper and we are going to offer the rest for discussion by just asking them. In light of these assessments, drawing attention, based on ontological knowledge relying on the wholeness of universe, to the question, on macro level planning, of whether or not the ontological realities of man, energy and movements of thinking can provide macro data for planning on a universal level as important factors affecting mankind will be one of the limited objectives of the paper.